ANALISIS PUTUSAN NOMOR 4/PID.SUS-ANAK/2021/PN.SRG OLEH ANAK YANG MENYALAHGUNAKAN NARKOTIKA : Analysis Of Decision Number 4/Pid.Sus-Child/2021/Pn.Srg By Children Who Abused Drugs - Savira Riska Prameswari; Azmi Syahputra (Reformasi Hukum Trisakti, 2024)
Children as drug abusers must undergo a criminal justice process, children who should not receive criminal justice should receive protection. The existence of a child protection law should be used as a reason to protect all deviant behavior carried out by children. The formulation of the problem in this research is about how the judge considers when imposing a prison sentence on a child who abuses narcotics and what the legal consequences are if the judge does not consider the child's social justice litmas in Decision No. 4/PIDSUS-Anak/2021/PN SRG. This research method uses a normative method, where secondary data is processed qualitatively and conclusions are drawn deductively. The results of the research and discussion illustrate that the judge's consideration of deciding whether a minor should be sentenced to imprisonment violates Law number 35 of 2014 concerning child protection in article 67, article 103 (1). The conclusion is that the legal consequences of the judge not considering the Child Child Protection Research Unit in the decision that there was a discrepancy resulted in the decision being null and void because it violated Law number 11 of 2012 in article 60 paragraph (4)